"العلاقة السببية بين سعر الصرف وسرعة دوران النقود في الجزائر دراسة قياسية ) 1990 – 2019 )" - بن سالم, بسي; عبد الجبار, دشري; عمار, بن ناصر (University of eloued جامعة الوادي, 2020)
تهدف هذه الدراسة الى البحث عن العلاقة السببية بين سعر الصرف و سعر دوران النقود في الجزائر، أما البيانات المستخدمة فهي بيانات سنوية للمدة(1990-2019) والتعرف على اتجاه العلاقة السببية بين متغيرات الدراسة (سعر الصرف و سعر دوران النقود)، كما أخضعت متغيرات الدراسة إلى اختبار جذر الوحدة، اختبار ديكي فولور المطور(ADF) و التي بينا أن سلسلة سعر الصرف مستقرة عند الفرق الاول و أما سلسلة سرعة دوران النقود مستقرة عند المستوى، وفي ظل ما عرفه النظام المصرفي الجزائري من تطورات نقدية، مع صدور قانون النقد و القرض الذي يعتبر نقطة تحول في النظام المصرفي وأخيرا تعديل قانون النقد و القرض بما يعرف بالتمويل غير التقليدي و عرفه الاقتصاد من توسع في الكتلة النقدية، وكما أظهرت نتائج اختبار انجل وغرانجر إلى وجود علاقة سببية قصيرة المدى تتجه من سعر الصرف الى سرعة دوران النقود ،واثبتت نتائج تقدير اثر متغيرات الدراسة على بعض البعض باستعمال طريقة المربعات الصغرى العادية الى وجود اثر متبادل ضعيف بين متغيرات الدراسة .This study aims to search for the causal relationship between the exchange rate and the velocity of money in Algeria. during the period (1990-2019 ) and to identify the direction of the relationship. The study variables(the exchange rate and the velocity of money) The study variables to the unit root test , chosen by the developer Dicky Fullr (ADF) , which showed the exchange rate in stable at the first difference ,while the speed of money circulation in stable at the level ,and in light of the technical developments that the Algerian banking system has known, with the issuance of the monetary and loan law that in considered a turning point in the banking system and finally the amendment of the Monetary and Loan Law with in known as unconventional financing and the economy playing it from the expansion of the monetary mass, The results of(Engel and Granger ) s test showed that there is a short term causal relationship that causal relationship that goes from the exchange rate to the speed of money circulating, and the results of estimating The effect of the study variables on each other by using the high pictorial squares method ,to the existence of a weak reciprocal effect between the study variables.
مذكرة ماستر اقتصاد كمي
Keywords: سعر الصرف , سرعة دوران النقود , العلاقة السبية; exchange rate, velocity of money circulation, causal relationship